A novel Fe-defect induced pure-phase Na4Fe2.91(PO4)2P2O7 cathode material with high capacity and ultra-long lifetime for low-cost sodium-ion batteries. (January 2022) - Zhao, Along; Yuan, Tianci; Li, Peng; Liu, Changyu; Cong, Hengjiang; Pu, Xiangjun; Chen, Zhongxue; Ai, Xiping; Yang, Hanxi; Cao, Yuliang
Abstract: Na4 Fe3 (PO4 )2 (P2 O7 ) (NFPP), as a typical cathode material of sodium ion battery, has great application prospect because of its low-cost, non-toxicity and appropriate working voltage and theoretical capacity. However, its poor electron and ion conductivities associated by non-erasable NaFePO4 impurity generated in all the synthesis methods limits the capacity utilization of NFPP. Herein, we report a novel pure-phase Na4 Fe2.91 (PO4 )2 (P2 O7 ) cathode material prepared simply by introducing a small amount of Fe defects in the lattice. The first-principles calculations reveal that Fe defects in the NFPP materials result in a lower band gap and migration energy barriers, thereby leading to a higher electron and Na + ion conductivity. As a result, the pure-phase Na4 Fe2.91 (PO4 )2 (P2 O7 ) cathode exhibits a high discharge capacity (110.9 mA h g −1 at 0.2 C), excellent rate performance ( 52 mA h g −1 at 100 C) and outstanding long cycle stability over 10, 000 cycles without discernible capacity decay. The pouch cell assembled with Na4 Fe2.91 (PO4 )2 (P2 O7 ) cathode and hard carbon anode, shows high capacity retention rate of 87.4% over 1000 cycles. These results suggest a feasible application of the simple defect regulation strategy to synthesize high-quality and pure-phase Na4 Fe2.91 (PO4 )2 (P2 O7 ) materials for low-cost sodium-ion batteries. Graphical Abstract: ga1 A novel and pure phase Na4 Fe2.91 (PO4 )2 P2 O7, for the first time, prepared by regulating Fe defects, which exhibits extraordinary structural stability and outstanding electrochemical performance for SIBs. Highlights: A novel pure phase Na4 Fe2.91 (PO4 )2 (P2 O7 ) is prepared by introducing Fe defects. The Na4 Fe2.91 (PO4 )2 (P2 O7 ) exhibits high Na-storage performance. The excellent performance is attributed to Fe defects and pure phase.